Mineral elemental composition Ofsyzygium Polyanthum (wight). Walp - Mohammad Moneruzzaman, Khandaker; Nur Fatihah, Hasan Nudin; Abd Manaf, Ali (2020)
Analysis of elemental composition of Syzygium polyanthum (Wight) Walp cultivars used by malay ethnic group as Ulam and traditionally for treatement of various ailments in Peninsular Malaysia. The elemental composition was determine using Inductively coupled plasma-mass spectrometry (Icp-Ms) and Neutron activation analysis (NAA) techniques. Standard reference material was used. Concentration of the following element Ca, Mg, Mn, Na, K, Fe, ZN, Co, Cu, Cr, Ni, V, Al, Ba and Pb were determined. Values are significantly difference at (pd<0.05). Presence of the elemental Ca, Mg, Mn, Na, K, Fe, ZN, Co, Cu, and Cr in the examined plant parts are responsible for lowering effects of glucose; making them to be hypoglycemic. The study is the first of its kind to present profile of trace elemental composition of Serai Kayu and Serai Kayu Hutan despite its acceptability by the malay populace. The findings of the study should be utilised in the development of herbal product to avioid over exploitation of the plants in Peninsular Malaysia.